Development of E-Scrapbook Media Containing Hot Listed Questions in Science Subjects - trinadia, dhea; Ida; H.M. Lubis , Patricia (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2024)
This research was motivated by students' lack of enthusiasm in the learning process, learning that was less interesting because the learning media was less varied, there was a lack of use of technology that existed at the school, teachers rarely related to the water cycle material in the environment around the school. This aim is to produce an E-Scrapbook media product containing hots-based questions in the science subject water cycle material for class V SD Negeri 08 Palembang that is valid, practical and effective. This research uses the Research and Development research method using the ADDIE method (analysis, design, development, implementation and evaluation). The results of this research obtained an average score for media experts of 72% with